Asset and linen monitoring information system framework for UTAR Hospital - Tan, Yan Bin (2025)

(untitled)
The proposed project is developed and designed an Asset and Linen Monitoring Information System Framework by using the Frappe Framework ERPNext for UTAR Hospital, addressing the need for efficient monitoring and tracking asset and linen inventory management. The traditional monitoring method of manually searching and checking assets and linens inventory used in hospital may be time-consuming and prone to human errors. It is leading to unnecessary losses on missing assets or linens and inefficiencies of monitoring and tracking asset and linen. This system offers a user-friendly interface with a dynamic dashboard that streamlines operational hospital and enhances management of asset and linen. It is allowing administrators and staff to monitor assets and linens effectively in real-time data collection. The integrated features of real-time alert and role-based access control fall short in existing system, which are played a crucial role in maintaining operational efficiency and system data security. This project aims to fill this gap by implementing a comprehensive system that tracks and monitors assets and linens as well as sends timely notifications for PPM of asset and updates on newly remarked items. It keeps all the relevant department personnel of UTAR Hospital informed promptly to take action on the notification and make decision. It is implemented the Frappe Framework ERPNext to develop a secure and efficient system supporting those functionalities. Through the proposed project, the management of assets and linens in UTAR Hospital has been enhanced, reducing losses on missing assets or linens and improving operational hospital efficiency. By implementation of the system, it assists the administrator and manager of UTAR Hospital to better monitor and track the assets and linen inventory in real-time.